System Reliability and Environment to Be Helped by Non‐Event Demand Response. Issue 11 (June 2016) - Fine, James; George, Simi; Moss, Steven
Abstract : Like a few other states, California is working to decarbonize the electric utility industry and the ground transportation sector by 2050 as part of efforts to stabilize the global climate.